Index-based agricultural insurance products: challenges, opportunities and prospects for uptake in sub-Sahara Africa - Ntukamazina, Nepomuscene; Onwonga, Richard N.; Sommer, Rolf; Rubyogo, Jean-Claude; Mukankusi, Clare Mugisha; Mburu, John; Kariuki, Rahab (Kassel University Press, 2017)
Agricultural insurance products have been piloted in Sub-Saharan Africa (SSA) to address climate related risks faced by farmers. However, these products in general face low rates of adoption in SSA. Factors and challenges that may explain the low uptake of index-based insurance products in SSA are reviewed in this paper with the objective of assessing and documenting (i) the insurance products available to farmers, (ii) factors influencing farmers to purchase insurance products, (iii) challenges limiting farmers accessing to insurance products and (iv) opportunities that can positively enhance uptake in SSA. This review reveals that area yield index insurance, index-based crop insurance and index-based livestock insurance have been piloted or implemented in the region. The uptake of these products was found to be positively correlated with on-farm income/savings, literacy, and family size with estimated coefficients of 0.211, 0.292 and 0.018, respectively; and negatively correlated with premium rate (−0.183), age of farmer (−0.058), land tenure (−0.800) and farm size (−0.167). Challenges that impede uptake of index-based products include weakness of regulatory environment and financial facilities, basis risk, quality and availability of weather data, capacity building of stakeholders (farmer, insurer, and regulator), and lack of innovation for local adaptation and scalability. The current gap between high promise and low uptake calls for farmer-driven product design, strong public-private partnerships and improved quality and availability of weather data.